Mapping school-based coach education requirements in the United States - Atkinson, O.; Bates, S.; Anderson-Butcher, D.; Mack, S.: Goodway, J. (International Sport Coaching Journal, 2023)
To date, there is a critical gap in our understanding of coach licensure and training requirements for school-based coaches across the United States. The current study categorizes the policy landscape for school-based coaches by examining public documents that outline state-specific (N = 51) coach training requirements. In addition, authors engaged in an in-depth curriculum and cost analysis of required coach trainings in the state of Ohio to better understand training topics, costs, time commitments, and state-specific compliance criteria guiding coach education. Findings indicated most states (n = 49, 96%) require training for coaches; however, governing bodies, training topics, and coach-specific training (i.e., assistant, volunteer, and middle school) varied significantly by state. Moreover, our curriculum and cost analysis revealed that licensure processes are costly and time-intensive, and training content predominantly focused on physical health and safety with less emphasis on social-emotional health and youth development. Findings have important education, practice, and policy implications for informing a national coach training agenda.